2008
DOI: 10.1038/oby.2008.441
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) and Risk of Recurrent Cardiac Events in Obese Postinfarction Patients

Abstract: Studies of recurrent coronary events in obese postinfarction patients show mixed results despite potential importance of obesity‐related pathophysiologic processes and associated markers in establishing and predicting risk. The study aim was to determine specific markers of recurrent risk in obese postinfarction patients. Nondiabetic patients of the Thrombogenic Factors and Recurrent Coronary Events (THROMBO) postinfarction study were classified according to BMI as normal weight (<25 kg/m2), overweight (25.0–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In Ikenaga et al's retrospective study, a high Lp(a) value (≥40 mg/dL) was found to be associated with a poor prognosis after AMI in 411 patients treated with PCI 25 . Meanwhile, Lp(a) was found to be an independent predictor with HR and 95% CI of 3.94 (2.11-7.35) in 215 obese post-infarction patients during 2-year follow-up 24 . A recent observational study including 176 patients with STEMI also found a significant association of elevated Lp(a) concentrations with one-year cardiovascular outcomes 27 .…”
Section: Accepted Manuscriptmentioning
confidence: 91%
See 3 more Smart Citations
“…In Ikenaga et al's retrospective study, a high Lp(a) value (≥40 mg/dL) was found to be associated with a poor prognosis after AMI in 411 patients treated with PCI 25 . Meanwhile, Lp(a) was found to be an independent predictor with HR and 95% CI of 3.94 (2.11-7.35) in 215 obese post-infarction patients during 2-year follow-up 24 . A recent observational study including 176 patients with STEMI also found a significant association of elevated Lp(a) concentrations with one-year cardiovascular outcomes 27 .…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…To date, Lp(a) has been suggested as a risk predictor in some special populations, such as acute coronary syndrome, stable or premature coronary artery disease (CAD), diabetes mellitus (DM), familial hypercholesterolemia (FH) or postmenopausal women [17][18][19][20][21] . Whether Lp(a) poses additional risk in patients with prior MI is still unclear and the existing studies with small sample size or short-term follow-up did not achieve consistent evidence [22][23][24][25][26][27] .…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…It also increases synthesis of PAI-1 by endothelial cells which further reduces plasmin levels [ 16 ]. Lp(a) is also believed to be involved in atherogenesis and studies have shown links between Lp(a) levels and cardiovascular risk [ 16 , 22 , 23 , 24 ]. A summary of the regulators of fibrinolysis is provided in Table 1 .…”
Section: Regulators Of Endogenous Fibrinolysismentioning
confidence: 99%